Clinical Characteristics of Patients With Pancreatic Cancer and Pathogenic ATM Alterations. Issue 2 (23rd January 2021) - Hannan, Zain; Yu, Shun; Domchek, Susan; Mamtani, Ronac; Reiss, Kim A
Abstract: The Ataxia-Telangiesctasia, mutated ( ATM ) gene is involved in a number of DNA damage repair pathways and confers an increased risk for pancreatic ductal adenocarcinoma (PDAC). In this retrospective study, we identified and profiled 22 patients with PDAC and a known somatic or germline pathogenic ATM alteration (case patients). These patients were matched 2:1 by age, stage, and year at diagnosis to patients with PDAC without known ATM alterations. The median overall survival in patients with ATM alterations was 40.2 months compared with 15.5 months in the control population (hazard ratio = 0.14, 95% confidence interval = 0.04 to 0.47, 2-sided P = .001). In multivariable analysis, these findings persisted after adjustment for receipt of platinum therapy and Eastern Cooperative Oncology Group status. These findings suggest that pathogenic ATM alterations may be prognostic for improved outcomes in patients with pancreatic cancer.